A balanced translocation disrupting BCL2L10 and PNLDC1 segregates with affective psychosis. Issue 3 (3rd June 2016) - Bouwkamp, Christian G.; Kievit, Anneke J. A.; Olgiati, Simone; Breedveld, Guido J.; Coesmans, Michiel; Bonifati, Vincenzo; Kushner, Steven A.
Abstract : Affective psychoses are a group of severe psychiatric disorders, including schizoaffective disorder and bipolar I disorder, together affecting ∼1% of the population. Despite their high heritability, the molecular genetics and neurobiology of affective psychosis remain largely elusive. Here, we describe the identification of a structural genetic variant segregating with affective psychosis in a family with multiple members suffering from bipolar I disorder or schizoaffective disorder, bipolar type. A balanced translocation involving chromosomes 6 and 15 was detected by karyotyping and fluorescence in‐situ hybridization (FISH). Using whole‐genome sequencing, we rapidly delineated the translocation breakpoints as corresponding intragenic events disrupting BCL2L10 and PNLDC1 . These data warrant further consideration for BCL2L10 and PNLDC1 as novel candidates for affective psychosis. © 2016 The Authors. American Journal of Medical Genetics Part B: Neuropsychiatric Genetics Published by Wiley Periodicals, Inc.